LANGUAGE STYLE IN TASYA FARASYA’S ADVERTISEMENT VIDEO YOUTUBE - SRI AYU ANISAFITRI; MEISURI MEISURI (State University of Medan, 2024)
Language style in advertisement was conduct on Tasya Farasya’s YouTube Video. The article aimed to investigate the types and describe the realization the language style in Tasya Farasya’s advertisement video YouTube. This research using William Well’s theory and qualitative descriptive method. The data source is YouTube videos and 50 styles of English advertisements were found as data. The result emerged with nine types of language style advertisement: Hard Sell (8%), Soft Sell (4%), Lecture and Drama (2%), Straightforward (10%), Demonstration (24%), Problem Solution (20%), Slice of Life (6%), Spokeperson (12%), and Comparison (14%). Each language style has a different communication style, the hard sell style shows promotional language, the soft sell style shows more subtle promotional language such as lots of stories, the lecture and drama language styles show the language of drama stories created by advertisers, the straightforward style shows honest language. A style shows the language influences the audience by promoting products while using it. The problem and solution style indicates language that points out the problem and then suggest a solution. Lifestyle dramas show language that involves their personal lives through the products they advertise. The spokesperson’s style indicates the advertising language that advertisers usually use. Finally, comparative style shows the language of comparing one product with another.